Allelopathic Effects of Paulownia and Poplar on Wheat and Maize Crops Under Agroforestry Systems in Doon Valley - Singh, Charan; Dadhwal, K. S.; Dhiman, R. C.; Kumar, Raj; Avasthe, R. K. (Indian Forester, 2012)
A study was conducted for 3 years (1998-2000) on the farmers’ fields in Doon Valley to evaluate the allelopathic effects of trees on the understory crops in a Paulownia and poplar based agroforestry system. Results revealed that leaf leachates of both tree species significantly affected germination of maize and wheat up to 21% and this negative effect was more with 2.0% concentration of leaf leachates in comparison to control. Further it was noticed that this effect was more pronounced with Poplar than Paulownia due to more tannin, wax, flavonoides and phenolics present in the leaf leachates of Poplar. Higher germination and growth parameters of wheat and maize were recorded with 1 and 2 per cent aqueous leaf extract of Paulownia - GP leaves. The Paulownia clone-GP out performed among all the clones of the two species without any significant negative effect on growth and yield attributes of maize and wheat which indicates its compatibility with crops. Thus, it is inferred that the Paulownia clone-GP has great potential as an agroforestry tree species in India under the similar Edapho-climatic conditions.